Captivity affects sperm production, testes size and beak color in House Sparrows ("Passer domesticus") - Lombardo, Michael P.; Thorpe, Patrick A. (Zielona Góra: University of Zielona Góra, Faculty of Biological Sciences)
We held 17 male House Sparrows in an outdoor aviary from May-July 2005 to repeatedly collect semen samples from them to be used later in the development of artificial insemination techniques. Birds were housed individually, but in visual and auditory contact with other House Sparrows of both sexes.
Keywords: captive studies; House Sparrow, "Passer domesticus"; spermatogenesis; testes; testosterone